Ověření vlivu rozpustných fenolických látek na aktivitu extracelulárních enzymů v rašeliništích - Kovářová, Lucie (Jihočeská univerzita, 2019)
The aim of the study was to verify the influence of the soluble phenolic compounds on the activity of extracellular enzymes. We tested the effect of aerobic and anaerobic conditions and addition of soluble phenolic compounds on potential activity of extracellular enzymes in two laboratory experiments. The results showed, that potential activities of oxidative extracellular enzymes such as phenol oxidase and peroxidase did not decline in anaerobic incubations, and have no oxygen requirement. Potential activities of hydrolytic enzymes was not inhibited by phenolic compounds and are oxygen related or have no oxygen relationship. No negative relationship between hydrolytic enzymes and phenolic compounds was observed. In summary, our results do not support the ''enzymatic latch'' hypothesis.
Verification of the influence of the soluble phenolic compounds on extracellular enzymes activities in peatlands
Keywords: rašeliniště; fenolické látky; extracelulární enzymy; oxidativní enzymy; hydrolytické enzymy; peatlands; phenolic compounds; extracelullar enzymes; oxidative enzymes; hydrolytic enzymes